Prognostic significance of carotid plaque presence in peritoneal dialysis patients and its association with the apolipoprotein B/apolipoprotein A1 ratio. Issue 12 (20th August 2020) - Chen, Yun; Shang, Da; Shao, Jie; Dai, Shuqi; Ge, Xiaolin; Hao, Chuanming; Zhu, Tongying
Abstract: Aim: Atherosclerosis has been reported as a risk factor for cardiovascular disease in the general population. As a phenotype of atherosclerosis, carotid plaque and its influence factors are rarely discussed among dialysis patients. The study aimed to investigate the prognosis‐predictive significance of carotid plaques in patients on peritoneal dialysis (PD), and explore risks factors for carotid plaque presence. Methods: It was an observational, prospective study. Patients that had undergone stable PD for at least 3 months were recruited and divided into two subgroups: group with carotid plaques and group without carotid plaques. Cox regression model was used to identify independent predictors of all‐cause mortality, cardiovascular events (CVEs), and cardiovascular mortality. Pathogenic factors correlated to the plaque‐occurrence were explored by logistic regression and verified by receiver operating characteristic (ROC) curve analysis. Results: A total of 233 PD patients were recruited. The cohort was followed for up to 86 months. The carotid plaque presence turned out to be an independent risk factor both of CVEs [hazard ratio (HR): 2.659; 95% confidence interval (CI): 1.231‐5.741; P = .013] and cardiovascular mortality (HR: 3.716; 95% CI: 1.168‐11.823; P = .026). The apolipoprotein B/apolipoprotein A1 (ApoB/ApoA1) ratio was significantly associated with the presence of carotid plaques. ROC analysis indicated that the area under the curve of the ApoB/ApoA1 ratio was higher than that of the traditional lipid metabolism index for detecting plaque presence. Conclusion: Carotid plaque presence can predict CVEs and cardiovascular mortality in PD patients. The ApoB/ApoA1 ratio is significantly correlated to the carotid plaques and the ApoB/ApoA1 ratio had a greater sensitivity than traditional lipid indices for predicting plaque presence. SUMMARY AT A GLANCE: The value of using the apolipoprotein B/apolipoprotein A1 ratio as an index of lipid metabolism compared with conventional lipid parameters was explored in people receiving peritoneal dialysis. The ratio independently associated with cardiovascular events and mortality and may be a better predictor of the presence of carotid plaques in this population.